An Improved Culture System of Mouse Peripheral Blood Lymphocytes for Analysis of Radiation-Induced Chromosome Aberrations. Issue 6 (12th September 2005) - Kanda, Reiko; Shang, Yi; Tsuji, Satsuki; Eguchi-Kasai, Kiyomi; Hayata, Isamu
Abstract : There is an incentive to develop a culture system of mouse peripheral blood lymphocytes (PBLs) to serve as models for studying genotoxic effects in humans exposed to mutagens, including ionizing radiation. However, many past approaches have been laborious, complex and only partly reproducible. In the present study, we established an improved culture system of mouse PBLs by removing blood and/or plasma, which was found to inhibit in vitro mitotic stimulation or proceeding cell cycles of lymphocytes. We compared the reactions of isolated PBLs to mitogens between the classical method and the present improved one. Then, we applied this method to the cytogenetic analysis using chemically induced premature chromosome condensation (PCC) as well as the conventional analysis, and demonstrated that the frequency of excess fragments observed in PCC cells might be useful to quantify the radiation-induced damages on chromosomes.